2018
DOI: 10.1159/000495680
|View full text |Cite
|
Sign up to set email alerts
|

miR-10b Downregulated by DNA Methylation Acts as a Tumor Suppressor in HPV-Positive Cervical Cancer via Targeting Tiam1

Abstract: Background/Aims: microRNAs (miRNAs) are known to act as oncogenes or tumor suppressors in diverse cancers. Although miR-10b is an oncogene implicated in many tumors, its role in cervical cancer (CC) remains largely unclear. Here, we investigated the function and underlying mechanisms of miR-10b in human CC. Methods: Quantitative RT-PCR was used to measure miR-10b expression in CC and normal tissues, and its association with clinicopathologic features was analyzed. Methylation of CpG sites in the miR-10b promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
1
16
0
4
Order By: Relevance
“…[41] Consistently, many studies implied that Tiam1 overexpression exhibited an accelerative effect in regulating malignant cell proliferation in a wide range of cancers, including hepatocellular carcinoma, [4244] oral cancer, [45] lung cancer, [35] esophageal cancer, [46,47] pancreatic cancer, [13,48] ovarian cancer, [49] cervical cancer, [33,50] colon cancer, [5154] gastric cancer, [55] osteosarcoma, [56,57] nasopharyngeal cancer, [14] laryngeal cancer, [31] and cholangiocarcinoma. [58] Besides, lots of studies indicated that upregulation of Tiam1 could protect malignant cells from apoptotic death in esophageal cancer, [46,47] cervical cancer, [50] laryngeal cancer, [31] retinoblastoma, [59] and colon cancer. [54] Third, a few recent studies demonstrated that Tiam1 was able to promote of angiogenesis cervical [33] and lung cancer.…”
Section: Discussionmentioning
confidence: 91%
“…[41] Consistently, many studies implied that Tiam1 overexpression exhibited an accelerative effect in regulating malignant cell proliferation in a wide range of cancers, including hepatocellular carcinoma, [4244] oral cancer, [45] lung cancer, [35] esophageal cancer, [46,47] pancreatic cancer, [13,48] ovarian cancer, [49] cervical cancer, [33,50] colon cancer, [5154] gastric cancer, [55] osteosarcoma, [56,57] nasopharyngeal cancer, [14] laryngeal cancer, [31] and cholangiocarcinoma. [58] Besides, lots of studies indicated that upregulation of Tiam1 could protect malignant cells from apoptotic death in esophageal cancer, [46,47] cervical cancer, [50] laryngeal cancer, [31] retinoblastoma, [59] and colon cancer. [54] Third, a few recent studies demonstrated that Tiam1 was able to promote of angiogenesis cervical [33] and lung cancer.…”
Section: Discussionmentioning
confidence: 91%
“…The stable expression of these two miRNAs inhibited Rac activation, cell growth, migration and invasion, as well as induced apoptosis by regulating TIAM1 expression. Furthermore, these results translated to mice as the expressions of miR-10a and miR-10b were found to reduce tumor growth and metastasis in esophageal squamous cell carcinoma [391] and cervical cancer [393], respectively. It was found that miR-10b was epigenetically silenced by DNA methylation [393,394], suggesting that demethylating agents could reactivate tumor suppressors to combat cancer progression.…”
Section: Mirna Targeting Of Rhogefsmentioning
confidence: 91%
“…Although originally identified as a Rac-specific GEF, studies have also identified GEF effects on RhoA and CDC42, albeit to a less efficient extent [226], where TIAM1 operates as a potent oncogene. Two members of the miR-10 family (miR-10a and miR-10b) have been shown to function as tumor suppressors by directly targeting TIAM1 [391][392][393][394]. The expression of these two miRNAs were found to be significantly reduced in tumor tissue compared to the matched normal tissue [391,393,394].…”
Section: Mirna Targeting Of Rhogefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most mature miRNAs inhibit gene expression by cutting target messenger RNA(mRNAs) or inhibiting mRNAs’ translation by binding to the 3 ’-UTRs of mRNAs. (6) More and more reports have shown that miRNA plays an important role in the proliferation, apoptosis, invasion and migration of tumor cells. Abnormal expression of miRNA can be used for tumor classification, diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%